Exploring low-income African American and Latinx caregiver perspectives on asthma control in their children and reactions to messaging materials. (3rd June 2022) - Zheang, Michelle; Rodriguez, Erin; Alvarado, Cinthia; Correa, Rebecca; Kahlor, Lee Ann; Matsui, Elizabeth C.
Abstract: Background: African-American and Latinx children suffer from higher rates of uncontrolled asthma and poorer outcomes compared to white children. Sociocultural factors play a prominent role in how caregivers navigate asthma control for their children. Objectives: (1) Explore the knowledge, perceptions and behaviors of Latinx and African-American caregivers related to their children's asthma and identify barriers to achieving asthma control; and (2) Elicit caregiver responses to messaging materials intended to help them better recognize uncontrolled asthma and seek timely medical treatment. Methods: Study participants were recruited and screened to meet the following inclusion criteria: African-American or Latinx race/ethnicity, household income at or below 185% of the federal poverty line, and at least one child diagnosed with asthma with symptom frequency consistent with uncontrolled asthma according to national guidelines. Participants attended one of three moderator-led focus groups. The transcripts were qualitatively analyzed using a thematic analysis approach. Results: Themes emerged among the nineteen participants related to asthma assessment, management, emotion, support, and trust. Caregivers exhibited gaps in their asthma knowledge, especially pertaining to the term "asthma control." Caregivers generally worried about asthma emergencies more than the daily impairments caused by uncontrolled asthma. Many were uncomfortable using daily controller medications, citing issues of provider trust and side effect concerns. Caregivers did not recognize uncontrolled asthma in their own child, even after viewing messaging materials informing them of symptom frequency criteria. Conclusion: Culturally tailored interventions, including public asthma messaging, should address low trust in provider recommendations and caregiver concerns about controller medications.